Analysis of Reproductive Strategies and Immunological Interactions in Batrachochytrium dendrobatidis-Resistant Japanese Tree Frogs - Ji-Eun Lee; Jun-Kyu Park; Yuno Do (Animals)
The amphibian chytrid fungus, Batrachochytrium dendrobatidis (Bd), has been implicated as an agent of acute declines in amphibian populations worldwide. East Asian amphibians have been coexisting with Bd for long periods and thus are considered resistant; among the many is the Japanese tree frog, Dryophytes japonicus. Our study focused Bd infection effects on reproductive behaviors and physiological parameters in D. japonicus as a function of better understanding the chronic effect of the disease on long-term population viability. During the peak breeding season, we captured 70 males and quantified the chorus size, calling behaviors, physiological states, innate immunity, and sperm quality of individuals. In a simple comparison, all parameters were not significantly different. However, in the NMDS analysis, we were able to confirm subtle trends in some items according to infection and correlations between several items. Importantly, sperm density and sperm vitality tend to increase with Bd infection load, suggesting increased reproductive effort following infection. Additionally, this analysis indicated that innate immunity was positively related to Bd infection intensities, indicating the activation of immunity upon infection. These findings indicate that Bd-resistant D. japonicus maintains reproductive capabilities and physio-logical stability despite Bd infection, likely due to a co-evolved immune system. The present work offers insight into how amphibian populations may have some endurance in the presence of Bd and points out the importance of studying resistant species as a means to understand long-term ecological effects. Our results suggest that resistance to Bd may not simply prevent cata-strophic declines but actively contribute to the dynamics of Bd prevalence in amphibian communities, and confer implications for conservation strategies.